1991
DOI: 10.1021/jm00110a019
|View full text |Cite
|
Sign up to set email alerts
|

2'-Deoxy-2'-methylenecytidine and 2'-deoxy-2',2'-difluorocytidine 5'-diphosphates: potent mechanism-based inhibitors of ribonucleotide reductase

Abstract: It has been found that 2'-deoxy-2'-methyleneuridine (MdUrd), 2'-deoxy-2'-methylenecytidine (MdCyd), and 2'-deoxy-2',2'-difluorocytidine (dFdCyd) 5'-diphosphates (MdUDP (1) MdCDP (2) and dFdCDP (3), respectively) function as irreversible inactivators of the Escherichia coli ribonucleoside diphosphate reductase (RDPR). 2 is a much more potent inhibitor than its uridine analogue 1. It is proposed that 2 undergoes abstraction of H3' to give an allylic radical that captures a hydrogen atom and decomposes to an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
149
1
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(157 citation statements)
references
References 0 publications
4
149
1
3
Order By: Relevance
“…In fact, we observed that the incubation of ML-1 cells with the nucleoside analog gemcitabine (dFdC) resulted in a signi®cant increase in the number of p53-positive nuclei in ML-1 cells. Gemcitabine has been demonstrated to be incorporated into DNA (Huang, 1991a); it may also cause the incorporation of mismatched deoxynucleotides into DNA because of the imbalance of cellular dNTP pools due to inhibition of ribonucleotide reductase by the drug (Gandhi and Plunkett, 1990;Baker et al, 1991). In the exponentially growing ML-1 cell population, approximately 19% of the cells had a strong p53 stain in their nuclei under normal culture conditions.…”
Section: Association Of the Wt P53 Protein With Dna Replication Activmentioning
confidence: 99%
“…In fact, we observed that the incubation of ML-1 cells with the nucleoside analog gemcitabine (dFdC) resulted in a signi®cant increase in the number of p53-positive nuclei in ML-1 cells. Gemcitabine has been demonstrated to be incorporated into DNA (Huang, 1991a); it may also cause the incorporation of mismatched deoxynucleotides into DNA because of the imbalance of cellular dNTP pools due to inhibition of ribonucleotide reductase by the drug (Gandhi and Plunkett, 1990;Baker et al, 1991). In the exponentially growing ML-1 cell population, approximately 19% of the cells had a strong p53 stain in their nuclei under normal culture conditions.…”
Section: Association Of the Wt P53 Protein With Dna Replication Activmentioning
confidence: 99%
“…dFdCTP directly inhibits DNA polymerase [6], cytidine triphosphate synthetase [7] and deoxycytidylate deaminase [8], and is incorporated into DNA, thereby terminating chain elongation [9]. dFdCDP potently inhibits ribonucleotide reductase (RR), thereby decreasing deoxynucleotide pools [10]. Despite its multiple intracellular targets, the resistance to gemcitabine often ensues [1].…”
Section: Introductionmentioning
confidence: 99%
“…3 Gemcitabine diphosphate (dFdCDP) binds to the large subunit M1 of RR (RRM1) and inhibits RR, thereby depleting the cellular deoxynucleotide (dNTP) pools. 4,5 RRM1 has been identified as the key molecule in determining the efficacy of gemcitabine. The overexpression of RRM1 had been repeatedly reported in gemcitabine-resistant cancer cells both in vitro and in vivo, [6][7][8][9][10][11] and RRM1 overexpression through the transfection of a lung cancer cell line led to gemcitabine resistance as well.…”
Section: Introductionmentioning
confidence: 99%